Announcement (Quarterly Journal of Economics, 2000)
Journal Article Announcement Get access The Quarterly Journal of Economics, Volume 115, Issue 1, February 2000, Page i, https://doi.org/10.1093/qje/115.1.i Published: 01 February 2000